2018
DOI: 10.1002/clc.22946
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors and outcomes of patients with pericardial effusion in chronic kidney disease

Abstract: In hospitalized CKD patients, hypocalcemia may be useful in identifying those with moderate to large pericardial effusion. In this population, pericardial effusion does not seem to be associated with adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…The collection of uremic toxins is likely to be the known cause of pericarditis. Furthermore, chronic buildup of the volume and hypoalbuminemia can also lead to non-inflammatory type pericardial effusion [ 7 ]. Patients with chronic kidney disease are also presented with uremic risk factors of cardiovascular disease such as increased oxidative stress, homocysteine, and lipoproteins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The collection of uremic toxins is likely to be the known cause of pericarditis. Furthermore, chronic buildup of the volume and hypoalbuminemia can also lead to non-inflammatory type pericardial effusion [ 7 ]. Patients with chronic kidney disease are also presented with uremic risk factors of cardiovascular disease such as increased oxidative stress, homocysteine, and lipoproteins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that among hemodialysis ESRD and chronic kidney disease patients, pericardial effusion is seen to be 14.3% [ 13 ]. However, a study by Ravi, Iskander [ 7 ] reported a relatively higher incidence of pericardial effusion among dialysis patients, 44%. In a recent retrospective study, Bentata, Hamdi [ 19 ] reported that the incidence of small, moderate and large pericardial effusion among ESRD patients were 31.2%, 37.6% and 31.2%, respectively, which was small 8(6.1%), moderate in 8(6.1%) and large in 1 (0.7%) case(s) in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,9 Alasan menegakkan diagnosis keperawatan kedua adalah pasien memiliki keluhan sesak napas saat beraktivitas. Berdasarkan patofisiologi, pasien GGK stadium akhir akan mengalami akumulasi toksin uremik yang tidak teridentifikasi karena gangguan metabolik meliputi uremia, hipokalsemia, hipoproteinemia, dan hiperurisemia, 14 serta adanya edema paru yang diakibatkan oleh tertimbunnya cairan serosa atau serosanguinosa secara berlebihan di dalam ruang interstisial dan alveoli paru 15 yang mengakibatkan sirkulasi oksigen ke seluruh jaringan tidak efektif, sehingga tubuh mengompensasi dengan napas pendek dan saat beraktivitas. 13 Penyebab lain intoleransi aktivitas pada pasien GGK yang sedang menjalani terapi hemodialisis adalah adanya reduksi kadar hemoglobin (Hb) dalam darah, sebagai akibat dari penurunan eritropoetin karena ginjal tidak mampu menyerap zat besi, sehingga mengganggu kemampuan pasien untuk beraktivitas sehari-hari.…”
Section: Pembahasanunclassified